2018
DOI: 10.15273/ijge.2018.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Rural Residents’ Satisfaction of Household Latrine and its Influencing Indicators: Evidence from Sichuan, China

Abstract: We conducted a second survey of household latrine based on the first survey study findings of rural facilities that toilet is the most significant influencing factor affecting farmers' satisfaction. The popularity proportion of rural sanitary latrines in China has been low, and the health of rural residents and the environmental sanitation in rural areas have not been effectively guaranteed. Factor analysis and logistic regression models are used to study the current situation of rural household latrines, rura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Satisfaction depends not only on the internal factors of households but also on the external environment. Therefore, based on some important studies in this field (such as [ 37 , 44 , 45 , 47 , 48 , 72 , 73 ]) and our sample data, we added the independent variables to our econometric models based on their relevance to our dependent variables.…”
Section: Methods and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Satisfaction depends not only on the internal factors of households but also on the external environment. Therefore, based on some important studies in this field (such as [ 37 , 44 , 45 , 47 , 48 , 72 , 73 ]) and our sample data, we added the independent variables to our econometric models based on their relevance to our dependent variables.…”
Section: Methods and Datamentioning
confidence: 99%
“…They found that ‘pick-up frequency by ‘waste collection vehicles’, ‘publicity and education’, ‘fund supply situation’, and ‘charging standard for waste treatment’ were the four principal determinants of respondents’ satisfaction with waste treatment. Ao et al [ 48 ] used factor analysis and a logistic regression model to analyze the indicators influencing rural residents’ satisfaction with rural household latrines in Sichuan, China. They found that respondents are relatively satisfied with rural household latrines, and their satisfaction is affected mainly by the basic condition of latrines, village committee performance, transparency of village affairs, sources and subsidies of funds, construction participants, and construction methods.…”
Section: Introductionmentioning
confidence: 99%